MODERN RUSSIAN AUTOBIOGRAPHICAL PROSE IN THE TIME SYSTEM - Wang Jiao (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2017)
In this article the main attention is paid to research into the narrator’s time and the autobiographical hero’s time in the Modern Russian autobiographical prose. First of all it gives outlines of the leading position of the time in the binarization of “time / space” and explanations for relationships of the narrator’s time and the autobiographical hero’s time. The epic time is described as the basic time of the narrator, which manifests itself mainly in two points - change or cessation of chronological movements of the hero. The biographical time is regarded as the dominant time of the autobiographical hero, in which growth and evolution of the hero occur. The study on intersection of the biographical time with historical, everyday and mythological times occupies a great place in the article.